Filming at the Rif: 1907-1927: Images from and for a Colonial Time - Martínez Álvarez, Josefina (Hispania Nova, 2021)
Cinema was part of Western "civilizing" activities from its beginning. The newsreels were a source of images that strengthened the sense of belonging, both in metropolitan cities and in colonies. From 1907 until the pacification of the Spanish Protectorate in Morocco in 1927, the cinema was present in the panish colonial action, since it opened the way to cultural assimilation, by dazzling the indigenous people. Those involved in its expansion showed their expectations about the power of cinema: the army, waiting for their victories to be celebrated; critics and directors, wanting to produce a great film about Spanish achievements in the modernization of North Africa; producers, willing to take advantage of new opportunities; and the public, eager to be thrilled with the magic and knowledge that is transmitted through the big screen.